Protection of human rights in Southeast Asia with special reference to the Rohingya in Myanmar: a critical study of the effect of ASEAN’s policy and action on ASEAN Intergovernmental Commission on Human Rights (AICHR) - Rachminawati, Rachminawati; Mokhtar, Khairil Azmin (2018)
Since its inception over four decades ago ASEAN has always worked towards improving the lives of its citizens. Year 2009 has opened another chapter with the inauguration of AICHR pursuant to Article 14 of the ASEAN Charter at the 15th ASEAN Summit. Since then AICHR has conducted various activities. In the midst of these ‘progress’ the vital question remains unanswered; To what extend AICHR has been successful in protecting human rights of citizens in ASEAN countries? This is a qualitative legal research. This study serves as an analytical basis to predict the future development of the AICHR as well as human rights protection in the region. Furthermore, it contributes to the reform of both ASEAN and AICHR toward implementation of human rights in the region. This research focuses on human rights issues of the Rohingya in Myanmar whereby ASEAN’s policy and action relating to the issue are examined. The finding shows that the policy and action of ASEAN does not provide much support in protecting the rights of the Rohingya. On the contrary the policy has hindered the effort of AICHR in protecting human rights. It is recommended that ASEAN and its member states should take real and concrete effort to protect human rights. AICHR is not really independent because it relies almost completely on ASEAN. For AICHR to realize its aims and objective ASEAN and its member states muct respect human rights and support AICHR with necessary power and measure